CoCrMo Metal-on-Metal Hip Replacements - Liao, Yifeng (2013)
After the rapid growth in the use of CoCrMo metal-on-metal hip replacements since the second generation was introduced circa 1990, metal-on-metal hip replacements have experienced a sharp decline in the last two years due to biocompatibility issues related to wear and corrosion products. Despite some excellent clinical results, the release of wear and corrosion debris and the adverse response of local tissues have been of great concern. There are many unknowns regarding how CoCrMo metal bearings interact with the human body. This perspective article is intended to outline some recent progresses in understanding wear and corrosion of metal-on-metal hip replacement both in-vivo and in-vitro. The materials, mechanical deformation, corrosion, wear-assisted corrosion, and wear products will be discussed. Possible adverse health effects caused by wear products will be briefly addressed, as well as some of the many open questions such as the detailed chemistry of corrosion, tribochemical reactions and the formation of graphitic layers. Nowadays we design almost routinely for high performance materials and lubricants for automobiles; humans are at least as important. It is worth remembering that a hip implant is often the difference between walking and leading a relatively normal life, and a wheelchair.